2013
DOI: 10.1002/uog.12506
|View full text |Cite
|
Sign up to set email alerts
|

Agenesis of the fetal corpus callosum: sonographic signs change with advancing gestational age

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 10 publications
5
79
1
1
Order By: Relevance
“…25,26 However, these signs might be subtle or missing. 27,28 The presence of a normal CC and its biometry has been assessed by transabdominal and transvaginal 2D and 3D sonography and with fetal MR imaging from 18 weeks onward. 10,17,[29][30][31][32][33] Indirect appreciation of the developing CC will be seen by demonstration of the pericallosal artery and its branches.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 However, these signs might be subtle or missing. 27,28 The presence of a normal CC and its biometry has been assessed by transabdominal and transvaginal 2D and 3D sonography and with fetal MR imaging from 18 weeks onward. 10,17,[29][30][31][32][33] Indirect appreciation of the developing CC will be seen by demonstration of the pericallosal artery and its branches.…”
Section: Discussionmentioning
confidence: 99%
“…The power Doppler examination of these vessels has been mostly reported in fetuses with suspected callosal agenesis using 2D ultrasound with the aim of confirming the sonographic findings [8]. In fact, due to the close anatomical relationship between the corpus callosum itself and its feeding vessels, the pericallosal arteries are not sonographically detectable in fetuses with complete callosal agenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Paladini et al, in the retrospective analysis of fetuses with CC defects, revealed that in most cases the abovementioned ultrasound signs were not present < 24 weeks of gestation. On the other hand, they were more evident with the advancing gestational age: VM was present in 74.3% and colpocephaly in 68.6% of the cases in the late second trimester [22]. Prediction of the long-term pregnancy outcome and neurodevelopment in childhood depends on the type of defect and presence of the associated anomalies.…”
Section: Agenesis Of Corpus Callosum (Acc)mentioning
confidence: 99%
“…On the other hand, the prognosis for fetuses with ACC and other anomalies remains poor. To sum up, prenatal detection of CC malformations presents a challenge due to the fact that sonographic signs may be very subtle or appear after the second-trimester scan [22]. Proper management requires thorough neurosonographic evaluation of CNS.…”
Section: Agenesis Of Corpus Callosum (Acc)mentioning
confidence: 99%